2006
DOI: 10.1111/j.1461-0248.2006.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Community maturity, species saturation and the variant diversity–productivity relationships in grasslands

Abstract: Detailed knowledge of the relationship between plant diversity and productivity is critical for advancing our understanding of ecosystem functioning and for achieving success in habitat restoration efforts. However, effects and interactions of diversity, succession and biotic invasions on productivity remain elusive. We studied newly established communities in relation to preexisting homogeneous vegetation invaded by exotic plants in the northern Great Plains, USA, at four study sites for 3 years. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…For example, Guo et al [14] showed that non-monotonic relationships between biomass production and grassland plant richness exist, but only when a wide enough range of richness is sampled. In our model, if the host community size is smaller than that required for the community to begin saturating (e.g., if host community <20 species in Figure 2D), an amplification effect would be the logical expected outcome of diversity loss, but this expectation would change if more speciose communities were sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Guo et al [14] showed that non-monotonic relationships between biomass production and grassland plant richness exist, but only when a wide enough range of richness is sampled. In our model, if the host community size is smaller than that required for the community to begin saturating (e.g., if host community <20 species in Figure 2D), an amplification effect would be the logical expected outcome of diversity loss, but this expectation would change if more speciose communities were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more realistic expectation might be that community abundance saturates with increasing richness. For example, saturation of total community biomass and percent cover has been documented in various plant systems [12][14]. Despite these observations, the effects of saturating host abundance on pathogen transmission have not been explored theoretically or empirically.…”
Section: Introductionmentioning
confidence: 99%
“…This approach differs from the original approach where 3-5 species of vegetation were used in the seed mix by including 16-32 species, a level that reaches a saturation point, thus, is more resistant to invasion of exotic species [36-38]. Similar to DNC, productivity and vegetation vigor within species-rich planted fields declines as the stand ages, however, proper disturbance of native vegetation that is adapted to the local environment and disturbance can eliminate the need to reseed plantings [15,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Low diversity plantings are more susceptible to invasion of exotic plant species and provide lower levels of productivity at maturity [38]. More diverse species rich plantings of 16–32 species in the Prairie Pothole…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation